Chronic non-specific low back pain and ankle proprioceptive acuity in community-dwelling older adults. (24th August 2022) - Xiao, Fangxin; Maas, Huub; van Dieën, Jaap H.; Pranata, Adrian; Adams, Roger; Han, Jia
Highlights: Decreased ankle proprioception in older adults with LBP compared with healthy peers. Older adults with LBP underestimate the extent of ankle inversion. Impaired central proprioceptive processing in older people with LBP. Abstract: Background: For people above 65 years old, low-back pain (LBP) is associated with balance problems and falls. Down-weighting of proprioception due to ageing and LBP may cause such balance problems. While lumbar proprioceptive deficits have been shown in LBP and indications for more generalized deficits have been found, ankle proprioception, which is crucial for balance control, has not been studied in people with LBP. Research question: Is there any difference in ankle proprioceptive acuity between community-dwelling older adults with and without LBP? We hypothesized that ankle proprioception was impaired in community-dwelling older adults with LBP compared to those without LBP. Methods: Thirty participants over 65 years old volunteered. Fifteen had LBP (M/F = 2/13, age = 72.0 (4.6) years), fifteen were healthy controls without back pain (control group) (M/F = 2/13, age = 72.1 (4.8) years). Ankle proprioception was measured in normal weight-bearing conditions, using the Active Movement Extent Discrimination Apparatus (AMEDA). Accuracy on the ankle proprioceptive test was expressed as absolute error (AE), constant error (CE) and variable error (VE). Results: AE was significantly larger ( P =  0.029, 95 % CI = [0.00, 0.90]) in the LBP group, CE was also significantly larger ( P =  0.046, 95 % CI = [-0.91, −0.01]), indicating an underestimation of ankle inversion in participants with LBP compared to controls. VE was not different between the two groups ( P  = 0.520, 95 % CI = [-0.20, 0.59]). No significant correlation was found between pain intensity and AE, CE or VE ( P  > 0.05). Conclusion: Ankle proprioception decreased in older people with LBP compared to healthy peers, suggesting impaired central proprioceptive processing. Older people with LBP underestimate the extent of ankle inversion, which may increase fall risk. Thus, evaluation and training of ankle proprioception may be useful in older people with LBP.